Management Model for Training of Pedagogical Competence for Lecturers With Non-Teacher Training Background at Stain in Central Java - Zaenal Mustakim (Postgraduate Program, Universitas Islam Negeri (UIN) K. H. Abdurrahman Wahid Pekalongan, Indonesia, 2016)
The Law of the Republic Indonesia number 14 2015 requires teachers -including lecturers- to have -among others- pedagogical competence. It has been said that a large number of lecturers at higher education institutions show low level of the competence. Although several training programs are conducted to improve their pedagogical competence, the result shows little significance. This calls for serious handling in the management of these training programs, especially ones designed for those with non-teacher training background. This study employs Research and Development approach. Data analysis was conducted using a descriptive model (interactive model) and paired t test/wilcoxon. This research results in a management model for pedagogical training programs for lecturers with nonteacher training background along with its practical manual. The management phases consist of planning, organizing, actuating, evaluating, and monitoring followed by follow-up programs. The research shows that the management model used for training of pedagogical competence is considered effective in enhancing the pedagogical competence of lecturers with non-teacher training background at STAIN in Central Java.